Analisis Risiko Usahatani Kedelai Di Kecamatan Jawai Selatan Kabupaten Sambas - Dewi Kurniati (Universitas Muhammadiyah Pontianak, 2014)
This research aimed to determine the risk of production and income in a group of farmers who use local seeds and farmers who use superior seeds in soybean farming. The research areas are in Sambas District, subdistrict of Jawai Selatan. The village sample selected is Sarang Burung Kolam Village with 31 farmers. Production and revenue risk analysed based on the value of coefficient of variation (CV). The analysis showed that the risk of production and income in a group of farmers who use local seeds is greater than the group of farmers who use superior seeds. The average of production and income soybean farming in group of farmers who use superior seeds is greater than the group of farmers who use local seeds.